Баптистерии Херсонеса (к истории крещального обряда в ранневизантийский период) - Завадская, И.А. (Материалы по археологии, истории и этнографии Таврии, 2002)
At present there are building remains of four baptisteries in Chersonesos. All of them were in the complex with basilicas dating back to the second half of the 6th - the beginning of the 7th centuries. All in all twelve churches of this epoch were discovered here. The baptistery in Uvarov basilica, the cathedral of the city, was notable for monumental and complicated structure (Fig. 1, li). Judging by the size and location of the font, it was intended for baptising adults. The opinion of S. A. Belyaev on the functional purpose of constructions being a part of the baptistery complex (6) were revised and, basing on analogies, a different scheme of baptistery ceremony was proposed in this article. It first stage (renouncement of the devil, etc.) was performed in rectangular vestibule, then a catechumen went to the main premises, where he was baptised in the baptismal font and then anointed in the central apse.